Meningkatkan Kemampuan Rasa Tanggung Jawab Anak Melalui Kegiatan Gotong Royong Di Sekolah ( PTK Di PAUD Oryza Sativa Kabupaten Kepahiang) - Domi, Domi; Asnawati, Asnawati; Haryono, Mimpira (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this study was to determine the increase in the ability of a sense of responsibility in children through mutual cooperation activities at PAUD Oryza Sativa, Kepahiang Regency. This study is a Classroom Action Research (CAR) or also called Classroom action research with the procedure used in the form of a cycle. The subjects of this study were children in group A at PAUD Oryza Sativa, Kepahiang Regency, totaling 20 children. The study was carried out in three cycles. Data analysis was carried out in qualitative and quantitative descriptions with the emphasis being used to determine the increase in the process expressed in a predicate, while quantitative analysis was used to determine the increase in results using percentages. The results of increasing the ability of a sense of responsibility in children using mutual cooperation activities at PAUD Oryza Sativa, Kepahiang Regency in cycle I with a percentage of 30.62%, in cycle II with a percentage of 56.25%, and cycle III with a percentage of 80.93%. The conclusion of the study is that using mutual cooperation activities can improve the ability of children to feel responsible at PAUD Oryza Sativa, as proven in cycle III where there was an increase with the percentage of achievement of 80.93% with the criteria of developing very well (BSB).